Pemberdayaan Kader Kesehatan dalam Penatalaksanaan Penyakit Diabetes Mellitus - Hatmanti, Nety Mawarda; Winoto, Priyo Mukti Pribadi; Salamy, Nanda Fadhilah Witris; Rusdianingseh, Rusdianingseh; Septianingrum, Yurike; Maimunah, Siti; Wardani, Erika Martining (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2023)
Posbindu health cadres are a group of health cadres formed by the Government in coordination with the Kebonsari Health Center as an extension of the health workers at the Health Center whose job is to coordinate health activities in the community with the Health Center. The purpose of this community service activity is to increase the knowledge and skills of health cadres so that a sustainable empowerment process can be carried out. The solution offered is to carry out early detection of random blood sugar level checks to capture people affected by diabetes mellitus. Education by providing handbooks for health cadres about diabetes mellitus and providing taichi exercise activities. Demonstration of making dragon fruit juice as a distraction therapy for people with diabetes mellitus. The results of the entire series of community service activities resulted in, among others: early detection of diabetes mellitus found as many as 18 people had random blood sugar levels more than normal, increased knowledge of health cadres from less to sufficient about diabetes mellitus, the community participated in taichi gymnastics well and cadres health can re-practice making dragon fruit juice. The results of the activities have provided changes and variations to the knowledge and abilities of health cadres, so it is hoped that health cadres can carry out ongoing education to the community.